2012
DOI: 10.5402/2012/926817
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral TLR-4 Agonist Injection Is Critical for Modulation of Tumor Microenvironment and Tumor Rejection

Abstract: The tumor microenvironment shelters a complex network of mechanisms that enables local Immunosuppression to support tumor growth. In this study we found that, B16F10 melanoma growth is inversely correlated with peritumoral infiltrate cell number and with cell numbers in draining lymph nodes. Tumor growth ensued even when a foreign antigen was expressed by B16F10 cells in the presence of naïve specific CD8 + T cells. Treatment with TLR agonists has shown to sometimes result in tumor regression, however, not alw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…They also suggested that the intratumoral injection could lead to the rapid activation of DCs as well as the infiltration of the T-cells in the tumor, which might be the reason for the observed tumor rejection. They concluded that it is mainly the DCs present in the tumor, rather than the macrophages, that are major targets for LPS activation …”
Section: Strategies To Reduce the Lps-induced Side Effectsmentioning
confidence: 99%
“…They also suggested that the intratumoral injection could lead to the rapid activation of DCs as well as the infiltration of the T-cells in the tumor, which might be the reason for the observed tumor rejection. They concluded that it is mainly the DCs present in the tumor, rather than the macrophages, that are major targets for LPS activation …”
Section: Strategies To Reduce the Lps-induced Side Effectsmentioning
confidence: 99%
“…Mice with subcutaneous glioblastoma or rats with subcutaneous glioma tumors treated with intratumoral LPS experience partial and complete tumor regression and these responses are lessened in T cell deficient animals (Chicoine et al., 2001; Won et al., 2003; Mariani et al., 2007). Similarly, intratumoral injection of LPS in B16 melanoma mice results in tumor regression in those mice with increased activation of DC and T cells (Maito et al., 2012). By contrast, another study on the same model reported that LPS only reduced tumor growth when given in the context of a GM–CSF–expressing whole‐cell vaccine (Davis et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…While systemic LPS administration causes severe side effects, intra-tumoral applications have been suggested previously (178). Several studies reported that TLR4 agonists have been successfully harnessed as adjuvants in several models of other tumor entities like malignant melanoma and clinically, in BCG immunotherapy (179,180). While in vitro activation of the surface TLRs 1/2 and 4 and the endosomal TLRs 3 and 9 has a similar activating effect on splenic DCs, in vivo data showed that stimulation of the surface TLRs 1/2 and 4 suppressed CD8+ T cell responses (181).…”
Section: Tlr4mentioning
confidence: 99%